2014
DOI: 10.1177/1071100714557154
|View full text |Cite
|
Sign up to set email alerts
|

Medial Displacement Calcaneal Osteotomy Using Minimally Invasive Technique

Abstract: This series suggests that minimally invasive calcaneal osteotomy surgery can achieve excellent union rates aiding correction of deformity with no observed neurovascular or soft tissue complications. For surgeons experienced in open surgery, there is a short learning curve after appropriate training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 10 publications
1
27
0
Order By: Relevance
“…Kheir et al found no paresthesia after percutaneous MDCO using a high-speed low-torque side cutting burr. 9 Only limited data on the precise optimal location of the calcaneal osteotomy are available, and these have not examined nerve outcomes specifically. Myerson et al 12 reported performing the osteotomy 1 cm posterior to the posterior process of the talus, but these investigators did not comment on nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…Kheir et al found no paresthesia after percutaneous MDCO using a high-speed low-torque side cutting burr. 9 Only limited data on the precise optimal location of the calcaneal osteotomy are available, and these have not examined nerve outcomes specifically. Myerson et al 12 reported performing the osteotomy 1 cm posterior to the posterior process of the talus, but these investigators did not comment on nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering the total length of the incision and exposure, it would be inappropriate to regard it as a minimally invasive technique for calcaneal displacement osteotomy. More recently, a percutaneous osteotomy technique using a Shannon burr was introduced (11). The technique uses a high-torque, low-speed, and saline-cooled Shannon burr with a small incision.…”
Section: Discussionmentioning
confidence: 99%
“…The technique was first developed using a low-speed, high-torque Shannon burr with a free-hand technique (11). In addition to the end cutting of an ordinary burr, a Shannon burr has a side-cutting function (Fig.…”
mentioning
confidence: 99%
“…MCO was performed with an oscillating saw inclined posteriorly approximately 45 degrees to the plantar surface of the hindfoot. Once the osteotomy was completed, the posterior fragment is shifted 1 cm medially [9]. The osteotomy was secured with 2 parallels K-Wires or with a 7.3 mm cannulated screw.…”
Section: Methodsmentioning
confidence: 99%